Peran Upah dan Pengalaman Kerja Terhadap Penyerapan Tenaga Kerja Wanita Pada Usaha Batu Bata di Kecamatan Kuala Kabupaten Nagan Raya - Badli, Saiful; Firman, Firman; Noviar, Helmi; Mardaleta, Mardaleta; Fadlianur, Azzahiri (Jurnal Ilmiah Ekonomi Terpadu (Jimetera), 2025)
This study analyzes the effect of wages and work experience on the absorption of female labor in the brick business in Kuala District, Nagan Raya Regency. This study used a sample of 41 respondents with data consisting of primary and secondary data. The method used in this research is multiple linear regression analysis. The results showed that simultaneously, wages and work experience have a significant effect on the absorption of female labor. However, partially, wages do not have a significant influence, while work experience has a significant influence on the absorption of female labor in the brick business in Kuala District, Nagan Raya Regency.